Pengembangan alat abadi speed blocking sebagai alat bantu latihan menepis penjaga gawang futsal - Abadi , Ahmad; Haris Satria, M. (Indonesian Journal of Physical Education and Sport Science, 2022)
The research objectives are 1) producing a abadi speed reaction tool as a tools for training the futsal goalkeeper’s blocking reaction speed. 2) Testing the appropriateness of the product being development. The imstruments used in this study included (1) assement sheets/questionnaires, (2) suggestions. The results of the validation of media experts showed 81%, results of the validation of futsal practitioner experts showed 84%, and results of the validation of measurement test experts showed 89%. The results of the small-scale trial questionnaire showed that score 85% in the very good category, and the results of the large-scale trial showed that score 98,7% in the very good category, can be said to be accepted from the results of large-scale product trials questionnaire conducted by athletes with a score of 98,7% so the product can be sait to be “accepted/eligible” in use.